Predictors of attrition in HIV-positive subjects with peripheral neuropathic pain - Davis, L.; Evans, S.; Fishman, B.; Haley, A.; Spielman, L. A. (AIDS care, 2004)
The objective of this paper was to identify predictors of attrition in a study designed to assess whether cognitive behavioural therapy (CBT) was more helpful than supportive therapy (SP) in reducing pain associated with peripheral neuropathy in HIV-positive patients. Sixty-one subjects were randomized into either CBT or SP for six weekly one-hour sessions. Twenty-eight subjects dropped out before week six. Demographic variables such as age, gender, ethnicity, socioeconomic status and level of education were not predictive of attrition. However, higher scores on the Hamilton Depression Inventory (HAM-D, 17-item) (t (59)=−0.09, p<0.05) were predictive. These findings suggest that while dropouts were not more physically ill (e.g. CD4 counts, viral loads and opportunistic infections were not statistically higher), they reported greater psychological distress.